Kinerja Aparatur Pemerintah Daerah dalam Rangka Pelayanan Publik - Darmanto '; Syarif Fadillah (JIANA ( Jurnal Ilmu Administrasi Negara ), 2010)
This article addresses how to assess public-sector service from the perspective ofgovernment official performance in the Depok local government as a case study. We examineperformance from the factors that focuses on discretion authority, change orientation , paternal-ism culture, service ethics, insentive system, and team work. The population in this research is theofficial at the office (dinas) in the local government, Depok, which is directly have a contact andcommunication with public. This research applies simple random sampling. Data collection tech-nique is using questionnaire with closed type given to the respondents. Data analysis methods usedin this research is quantitative descriptive analysis. This study shows that the public service per-formance of the government officials in the local government, Depok in general is fairly good.Support if incentive system therefore must be improved.